2022
DOI: 10.3390/jmse10020201
|View full text |Cite
|
Sign up to set email alerts
|

Stock Assessment and Rebuilding of Two Major Shrimp Fisheries (Penaeus monodon and Metapenaeus monoceros) from the Industrial Fishing Zone of Bangladesh

Abstract: The two economically important shrimp species in Bangladesh are the tiger shrimp, Penaeus monodon, and the brown shrimp, Metapenaeus monoceros. However, a continuous decline in the landing of these species from the industrial trawling made it critical to assess their stock biomass status to explore their response to the present degree of removal. Given the minimum data requirement and robustness, this study employed the depletion-based stock reduction analysis (DB-SRA) to assess these fisheries rigorously. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
3
6
2
Order By: Relevance
“…Tiger shrimp is a desired item in the export market [8], but the stock is now heavily overfished. These results are generally consistent with some previous studies on major industrial shrimp stocks [1,7,8,10], which found that the biomass of tiger shrimp population is suffering from depletion, as are other main commercial fish species, which corresponded to the lowered CPUE trend in finfish in the historical catch along Bangladesh marine waters [59].…”
Section: Stock Condition Analysis Based On Lbb Approachessupporting
confidence: 91%
See 3 more Smart Citations
“…Tiger shrimp is a desired item in the export market [8], but the stock is now heavily overfished. These results are generally consistent with some previous studies on major industrial shrimp stocks [1,7,8,10], which found that the biomass of tiger shrimp population is suffering from depletion, as are other main commercial fish species, which corresponded to the lowered CPUE trend in finfish in the historical catch along Bangladesh marine waters [59].…”
Section: Stock Condition Analysis Based On Lbb Approachessupporting
confidence: 91%
“…Table 5 showed that the present and previous study's results vary in all parameters. Particularly for tiger shrimp, a significant variation is observed in K and r. The estimated K values by Barua et al (2020) [8] and Alam et al (2022) [7] were much lower than the present study. However, the 95% confidence intervals of their estimates of K overlapped with the range of this study's estimates.…”
Section: Stock Condition Analysis Based On Jabba Modelcontrasting
confidence: 75%
See 2 more Smart Citations
“…These previous studies were carried out using length-frequency data only by applying FAO-ICLARM stock assessment tools (FiSAT) to elucidate stock exploitation status but the spawning stock biomass, population percentage related to exploitation, and selectivity pattern were not considered. Moreover, in Bangladesh, commercial marine fisheries are mainly operated by earmarking fishing areas, limiting fishing days, mesh size regulation of gears, closure of spawning grounds, and fishing bans during spawning seasons [14,[20][21][22]. However, the implementation of fishing ban activities only during the propagation period is not as effective [23] as associated with implementing a catch quota for sustainable management of fisheries.…”
Section: Introductionmentioning
confidence: 99%